Pulmonary cement embolism following cement-augmented pedicle screw fixation in a patient with metastatic vertebral compression fracture: A case report and management considerations - Mohammad Daher, BS; Victor Percheron, MD; Adrien Lampilas, MD; Amer Sebaaly, MD; Guillaume Riouallon, MD; Stéphanie Bonhomme, MD; Maxime Delrue, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
We report the case of a 61-year-old female with metastatic rectal adenocarcinoma who underwent surgical fixation and laminectomy for an L3 vertebral compression fracture. Pedicle screws were augmented with cement. Follow-up computed tomography later detected an incidental pulmonary cement embolism in the right pulmonary artery. The patient remained asymptomatic and was managed with anticoagulation therapy. Subsequent gastrointestinal bleeding required temporary cessation of anticoagulation, but prophylactic anticoagulation was resumed due to the persistent embolus. At 6-month follow-up, the patient remained stable without hemorrhagic complications. In asymptomatic central pulmonary cement embolisms, anticoagulation may be appropriate but requires careful risk assessment and multidisciplinary management to balance the risks of thrombosis and bleeding.